Recurrent liver cyst. Case report and literature review. - Mitrović, Nebojša; Trifunovic, Nemanja S.; Jašarović, Damir; Stevanović, Dejan; Aleksandrić, Goran (Medical Research, 2024)
Introduction: Liver cysts are defined as cavities within the liver tissue, surrounded by a layer of epithelium and filled with liquid or semi-liquid contents. Mostly, they are asymptomatic and usually diagnosed by ultrasonography, CT or MR diagnostics. Symptoms occur as a result of complications such as bleeding, rupture, infection or compression of the biliary tract. All liver cysts can be divided into: 1. Infectious and 2. Non-infectious liver cysts. The most common non-infectious cysts are simple congenital biliary cyst.Case report: We present a 74-year-old female patient. She had upper right abdominal pain and dyspepsia several weeks before first examine. Abdominal ultrasound and CT verified a large simple cyst of the right lobe of the liver about 14cm in size. She underwent a minimally invasive surgery when a partial cyst resection was performed. After 7 months abdominal ultrasound, MR and MRCP verified simple reccurent cyst in right lobe about 13cm in size without communication with biliary system. She underwent open surgery when pericystectomia cum omentoplastica was performed. The pathohistological result is a benign biliary cyst. At regular follow ups without recurrence 12 months after procedure. Conclusion: There are many treatment modalities and each one is accompanied by certain disadvantages.  In recent years, conventional open surgical procedures have been replaced by minimally invasive surgical procedures. Laparoscopic surgery is the method of choice in carefully selected patients. Open conventional surgery is reserved for patients with giant cysts, recurrent cysts, deep intraparenchymal cysts, and right lobe subphrenic cysts.
Keywords: Reccurent cyst, Cystis hepatis, Liver cyst, Biliary cyst, Benign cyst, Pericystectomy